Recent Advances in Understanding and Use of Oleofoams - Fameau, Anne-Laure; Saint-Jalmes, Arnaud (Frontiers in Sustainable Food Systems, 2020)
This review aims at presenting recent advancements on the understanding of oleofoams for food applications. Edible oleofoams are currently based on heating a vegetable oil solution containing a high-melting point component, which crystallize upon cooling. After aeration (mostly by whipping), crystals adsorb to air bubble surfaces. The remaining crystals in excess in the continuous phase form an oleogel. Due to both the presence of crystals at the interface and in the bulk, the resulting oleofoams exhibits high stability to drainage, coalescence and disproportionation. The mechanisms leading to the high foam stability are still under investigations to understand and to discriminate between bulk and interfacial rheology effects. The research on edible oleofoams are still scarce in comparison to aqueous food foams even if they present promising applications. In the area of molecular gastronomy, oleofoams are already produced. Oleofoams are a great opportunity for food technologists to develop healthier food products with a low fat content associated to new sensorial properties. However, it is important to better understand these systems in order to help food technologists to use oleofoams and it will contribute to expand this new promising area in food science.